Tindak Pidana Korporasi Dalam Perspektif Kebijakan Formulasi Hukum Pidana - Rully Trie Prasetyo; Umar Ma’ruf; Anis Mashdurohatun (Jurnal Hukum Khaira Ummah, 2017)
The role of corporations dominates everyday life, let alone increased privatization. It is no longer the country that provides the needs, but the corporation. Corporations can increase state and labor wealth, but the revolution of economic and political structures has grown large corporate corporations too dependent on corporations so that countries can be dictated to their interests. Based on the above background, then the problem arises how the current criminal law formulation policy in the face of corporate crime, then how the application of criminal law enforcement for this against corporations that conduct criminal acts and how the policy of criminal law formulation in the face of corporate criminal acts in the future which will come. The research method used in this thesis is normative juridical by using secondary data. Data collection is done by collecting and analyzing library materials and related documents. Furthermore, the data are analyzed normatively qualitatively by way of interpreting and constructing statements contained in documents and legislation. The conclusion of this study is that the regulation of corporate criminal sanctions contained in the four laws is inconsistent. The inconsistency in the determination or imposition of the maximum penalty imposed on corporations is also the absence of uniformity in determining when a corporation can be said to commit a criminal offense, uniformity in the arrangement of who may be accountable or prosecuted and convicted, as well as the formulation of a criminal type that may be imposed on corporation that commits a crime.Keywords: Corporation Criminal Action, Formulation Policy, Criminal Law